2004
DOI: 10.1007/s00339-003-2406-z
|View full text |Cite
|
Sign up to set email alerts
|

Light-emitting silicon pn diodes

Abstract: We report on the electrical and optical characteristics of silicon light-emitting pn diodes. The diodes are prepared by ion implantation of boron at high doses and subsequent hightemperature annealing. Under forward bias, the diodes emit infrared electroluminescence closely below the band gap of bulk Si. We present a rate-equation model for bound excitons, free excitons and free carriers which successfully describes the electrical and optical behaviour of the diodes at low temperatures. Especially, an electric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 31 publications
2
9
0
Order By: Relevance
“…The temperature results agree well with other authors EL [4,5] measurements and previously reported EL and PL [3].…”
Section: Resultssupporting
confidence: 94%
See 2 more Smart Citations
“…The temperature results agree well with other authors EL [4,5] measurements and previously reported EL and PL [3].…”
Section: Resultssupporting
confidence: 94%
“…Implantation damage is reduced by subsequent annealing. This method has been shown to produce efficient devices compatible with standard ultra large scale integration (ULSI) processing technology [3][4][5] with increased electroluminescence (EL) efficiency at room temperature. The proposed model for the increased EL efficiency of this material at room temperature is the introduction of dislocation loops which improves carrier confinement [3,6], excitonic traps which store and supply electron -hole pairs at elevated temperatures have also been suggested [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2. These temperature results agree well with previously reported electroluminescence (EL) and PL [3] and other authors EL [1,3] measurements on similar material. However, such results are anomalous and in contrast to the PL results for normal silicon substrates or other III-V compound materials, which show the apparent decrease in PL intensity with increasing temperature.…”
Section: Methodssupporting
confidence: 94%
“…Ion implantation of boron into an n-type substrate to form p-n junction and recrystalization by annealing fabricate the diode material studied here. This method has been shown to produce efficient devices compatible with standard ultra large scale integration (ULSI) processing technology [1][2][3] with increased electroluminescence (EL) efficiency at room temperature. The proposed model for the increased EL efficiency of this material at room temperature is the introduction of dislocation loops which improves carrier confinement [3,4], although excitonic traps which store and supply electronhole pairs at elevated temperatures [5] and high bulk Shockley-Read-Hall lifetimes [6] have also been suggested.…”
Section: Introductionmentioning
confidence: 99%